Implementing Multicultural Education with Building Human Resources - Syahputra, Refi; Simatupang, Wandana; Sanawi, Fahrul; Daulay, Nurika Khalila; Azmi, Fachruddin (Edumaspul: Jurnal Pendidikan, 2022)
Plurality, diversity, and variation as well as public and cultural multiform in the international arena, especially in the very pluralistic Indonesian society, is a reality of necessity. Plurality and diversity have led to negative excesses and critical risks recently including collisions. Public and local culture in various places in Indonesia. Therefore it is important to anticipate, among others, the reliability of strong Human Resources (HR). Implementation of the development of various sectors such as the nature of resources, material and financial will not provide optimal implications for improving welfare, if it is not supported by adequate availability of reliable human resources, both in quality and quantity. The greatness of HR is not only in the concept but how to implement it properly and correctly. The data used is qualitative. This study references and explores relevant literacy, in nature to analyze the data the method used is to reduce data, present data, and conclude and examine research results on an ongoing basis in the research process. The research results show that; The progress achieved by a nation is supported by qualified human resources. HR development is principally directed towards increasing the participation and implementation of HR, which in turn will increase performance productivity. The world of academia, in carrying out multicultural education, must have a strong and qualified foundation, especially in the field of human resources, is no exception.